What factors can influence children’s perception of forests today and in the future? - de Sousa, Thiago Braz Barbosa; da Silva, Taline Cristina; Ramos, Marcelo Alves (Ethnobiology and Conservation, 2021)
Ethnobiological studies regarding the environmental perception of children are still infrequent, creating a gap in the understanding of the factors that influence the process of developing perception in this phase of life. Therefore, this study sought to verify the influence of some factors, such as contact with natural environments, gender, and age, in the representation of elementary school students, aged between 11 and 15 years, about remnants of the Atlantic Forest, at present and future. We observed that the elements represented by children did not differ in terms of contact with natural environments, but those who live in rural areas, represented more elements of degradation. In addition, the children studied here did not show significant differences in environmental representations between genders, and the increase in age indicated the loss of ecological knowledge about the natural components of a forest environment, giving space for a more utilitarian and degraded view of it. In general, we can state that children have precise perceptions about forest environments, and a negative perspective regarding the future of forests. Furthermore, certain factors may come to have a strong influence on their perception, especially with advancing age and the strengthening of social roles established culturally for different genders, which will strongly influence decision-making in favor of forests in the future.